2020
DOI: 10.1097/iae.0000000000002557
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Macular Capillary Loss in Patients With Uncontrolled Type 1 Diabetes

Abstract: Purpose: To analyze the evolution of macular vessel density (VD) over 1 year, during early worsening of diabetic retinopathy, in patients with uncontrolled Type 1 diabetes (T1D). Methods: Retrospective study of 12 eyes of 9 patients with T1D with early worsening of diabetic retinopathy imaged with optical coherence tomography angiography. The following data were collected at the time of pan retinal photocoagulation initiation and after 6 and 12 months: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 33 publications
1
6
0
1
Order By: Relevance
“…Our DM2 patients had a short disease duration (2.50 ± 2.88 years, range 0–11 years), which could explain the smaller changes in the VD at the DCP or they had an early diagnosis, before the signs became more severe. These results suggest that VD diminished with the progression of DM2, its duration and with the aging of the patient, as described by Lavia et al [ 56 ] and Ciloglu et al [ 57 ]. Most likely, this loss in the C area of the DCP will be reflected over time by an increase in the FAZ area in the DCP and a potential decrease in the BCVA.…”
Section: Discussionsupporting
confidence: 80%
“…Our DM2 patients had a short disease duration (2.50 ± 2.88 years, range 0–11 years), which could explain the smaller changes in the VD at the DCP or they had an early diagnosis, before the signs became more severe. These results suggest that VD diminished with the progression of DM2, its duration and with the aging of the patient, as described by Lavia et al [ 56 ] and Ciloglu et al [ 57 ]. Most likely, this loss in the C area of the DCP will be reflected over time by an increase in the FAZ area in the DCP and a potential decrease in the BCVA.…”
Section: Discussionsupporting
confidence: 80%
“…The study has shown that low VD around the optic disc is related to high FBG levels [ 8 ]. Lavia found a rapid decrease in macular VD over 12 months that was associated with a rapid improvement in blood glucose levels [ 19 ]. Among the groups with different HbA1c levels, we found that there were significant differences between the VDs of the control group and other groups, but there was no significant difference among the other four groups.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, OCTA implemented with projection artifact removal (PAR) software has shown that, in diabetic retinopathy, capillary drop-out affects the three capillary plexuses of the macula, although VA may remain normal up to a threshold of capillary drop-out which remains to be determined [8,9]. In a previous study, we have confirmed with OCTA the histological finding that the VD of the superficial vascular plexus (SVP) was proportional to the thickness of the corresponding retinal cellular layer in healthy subjects [10].…”
Section: Introductionmentioning
confidence: 99%